Graphene Quantum Dots-Capped Magnetic Mesoporous Silica Nanoparticles as a Multifunctional Platform for Controlled Drug Delivery, Magnetic Hyperthermia, and Photothermal Therapy - Yao, Xianxian; Niu, Xingxing; Ma, Kexin; Huang, Ping; Grothe, Julia; Kaskel, Stefan; Zhu, Yufang (Small, 2017)
A multifunctional platform is reported for synergistic therapy with controlled drug release, magnetic hyperthermia, and photothermal therapy, which is composed of graphene quantum dots (GQDs) as caps and local photothermal generators and magnetic mesoporous silica nanoparticles (MMSN) as drug carriers and magnetic thermoseeds. The structure, drug release behavior, magnetic hyperthermia capacity, photothermal effect, and synergistic therapeutic efficiency of the MMSN/GQDs nanoparticles are investigated. The results show that monodisperse MMSN/GQDs nanoparticles with the particle size of 100 nm can load doxorubicin (DOX) and trigger DOX release by low pH environment. Furthermore, the MMSN/GQDs nanoparticles can efficiently generate heat to the hyperthermia temperature under an alternating magnetic field or by near infrared irradiation. More importantly, breast cancer 4T1 cells as a model cellular system, the results indicate that compared with chemotherapy, magnetic hyperthermia or photothermal therapy alone, the combined chemo-magnetic hyperthermia therapy or chemo-photothermal therapy with the DOX-loaded MMSN/GQDs nanosystem exhibits a significant synergistic effect, resulting in a higher efficacy to kill cancer cells. Therefore, the MMSN/GQDs multifunctional platform has great potential in cancer therapy for enhancing the therapeutic efficiency.
CRIS-Team Scopus Importer:2022-04-14
Keywords: graphene; magnetic hyperthermia; mesoporous nanoparticles; photothermal effect